W jakim sensie i w jakim stopniu kontakty językowe "warunkują" zmiany językowe? = In what sense and to what degree do language contacts induce language change? - Kotin, Michail L. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Language contacts are, according to the "opinio communis" in contemporary linguistic theory, one of the most important reasons for language change. Linguists often claim that nearly every language feature can, in principle, be changed, if triggered by language contact.
Keywords: kontakty językowe; zmiany językowe; przemiany gramatyczne; kategoria określoności/nieokreśloności; language contacts; language change; grammatical change; definiteness/indefiniteness category